Continuous Metal-Insulator Transition and Scale Lawsin Metallic n-Type InP - Ennajih, D.; Mabchour, H.; El kaaouachi, A.; Echchelh, A.; El oujdi, A.; Mounir, E.; Ait Hammou, B.; Dlimi, S.
We have studied the transport properties in metallic n-type InP semiconductor. We show that the dependence on temperature of metallic electrical conductivity obey to the law =(=0)+1/2. We highlight the absence of a minimum electrical conductivity proposed by Mott at the metal-insulator transition. We show that the conductivity at temperature T = 0 K, (=0) , follows a scaling law as a function of the effective parallel and perpendicular Bohr radii ∥ and ⊥.
Keywords: Physics